Plasmapheresis in Myasthenia Gravis Crisis - Rifani Masharto, Alegra; Lubis, Bastian; Lubis, Andriamuri Primaputra; Nadeak, Rommy (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2023)
Introduction: Myasthenic crisis is the most lethal complication of myasthenia gravis. Referral to an intensive care unit is crucial in managing the myasthenic crisis. Hereby, we report a case of a myasthenic crisis in a 30-year-old female who underwent plasmapheresis. The patient underwent a 12-hour procedure for plasmapheresis and was discharged to a normal ward the next day. Although plasmapheresis is costly, its efficacy should be considered as the main treatment for myasthenic crisis. Case Illustration: Female, 30 years old, weighed 60 kgs, with myasthenia crisis. The patient came to an emergency department and was then intubated before being admitted to the intensive care unit. The physical diagnostic was normal and laboratory findings were leukocytosis. The patient was treated with normal saline, antibiotics, high-dose corticosteroids, and pyridostigmine. The patient was done plasmapheresis with synchronized intermittent mandatory ventilator mode. The patient was examined every 30 minutes. The physical examinations were relatively normal. The plasmapheresis procedure was ended in 12 hours. From the literature, plasmapheresis was found to have significant results for myasthenia gravis compared to conventional therapy because of its blood separation technique to remove autoantibodies. The next day patient was extubated with normal physical examinations and normal laboratory findings. The patient then moved from the intensive care unit to the normal ward and outpatient on the third day of hospital stay. The patient was given oral medicine that included antibiotics, corticosteroids, and pyridostigmine. Conclusion: From this case, we can see that plasmapheresis therapy has a really good outcome compared to other conventional therapy. However this therapy is expensive, so most healthcare providers don’t cover the payment. Hopefully, most hospitals and healthcare providers can cover up for this treatment to save many myasthenia gravis crisis. Keyword: Intensive Care Unit; myasthenic crisis; myasthenia gravis; plasmapheresis; treatment efficacy